2021
DOI: 10.1088/1755-1315/802/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Social impacts of oil spills towards the people living in coastal areas

Abstract: Soil and water contamination due to oil spills have caused a decline in soil and water quality and has undermined the welfare and health of people. The oil spills have affected the environment and ecosystem-based services, increasing the level of poverty and physical, mental, and occupational mobility of the people. One of the effects experienced by the people is the loss of livelihood, thus requiring them to change occupations, and some even become unemployed. The lack of support for livelihood and unemployme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, a study showed that the livelihood shift of the shermen to meet their daily needs was still not su cient or lower compared with what they earned in shing before the oil spills. Therefore, solutions required to overcome the impacts of the oil spills are through the distribution of nancial subsidies, the protection and care of those impacted by the oil spill, infrastructure compensation, participation in decision-making, and the involvement of the people (Alvernia et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study showed that the livelihood shift of the shermen to meet their daily needs was still not su cient or lower compared with what they earned in shing before the oil spills. Therefore, solutions required to overcome the impacts of the oil spills are through the distribution of nancial subsidies, the protection and care of those impacted by the oil spill, infrastructure compensation, participation in decision-making, and the involvement of the people (Alvernia et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The challenges of pipeline vandalization can be curbed through dialogue with the residents of these areas, infrastructure and human development, and implementation of sustainable oil exploitation and environmental management in the areas. Alvernia et al (2021) suggested some alternative actions needed to mitigate the effects of oil spills, including distribution of allowances for elderly people, safety and care of those affected by the spill, infrastructure remuneration, and involvement of residents in decision-making and citizen engagement.…”
Section: Policy Measures Available For Mitigating the Incidence Oil S...mentioning
confidence: 99%
“…Moreover, the incident made the participants realize the need for skills training to have an alternative source of income in times of disaster, when fishing is not allowed. However, Alvernia et al [45] showed that a livelihood shift of fishermen to meet their daily needs was still not sufficient or was less than what they earned from fishing before an oil spill. Therefore, the solutions required to overcome the impacts of an oil spill are through the distribution of financial subsidies, the protection and care of those impacted by the oil spill, and the involvement of those affected people [45].…”
Section: Perceived Socioeconomic Impacts Of Oil Spill To Fisherfolkmentioning
confidence: 99%